Associations of Early COVID-19 Cases in San Francisco With Domestic and International Travel. (21st May 2020) - Gu, Wei; Deng, Xianding; Reyes, Kevin; Hsu, Elaine; Wang, Candace; Sotomayor-Gonzalez, Alicia; Federman, Scot; Bushnell, Brian; Miller, Steve; Chiu, Charles Y
Abstract: In early-to-mid March 2020, 20 of 46 (43%) COVID-19 cases at a tertiary care hospital in San Francisco, California were travel related. Cases were significantly associated with travel to either Europe (odds ratio, 6.1) or New York (odds ratio, 32.9). Viral genomes recovered from 9 of 12 (75%) cases co-clustered with lineages circulating in Europe.